2005
DOI: 10.1109/jqe.2005.845925
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of tunable photonic crystal devices comprising liquid crystal materials as defects

Abstract: Abstract-The tuning properties of two-dimensional dielectric and metallic photonic crystals, which contain nematic liquid crystal materials as defect elements or layers, are thoroughly analyzed using appropriate formulations of the finite difference time domain (FDTD) method. Our methodology correctly incorporates the anisotropy introduced by the liquid crystal materials together with the dispersive properties of the metallic elements; it is used for calculating both the dispersion diagrams of the defect-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 25 publications
1
26
0
2
Order By: Relevance
“…In particular, photonic band structure computations have shown that controlling optical anisotropies allows for the opening and closing of complete threedimensional photonic band gaps in liquid crystal infiltrated PBG materials [14]. Later, the concept of tunable photonic band structures has been extended to tunable superrefractive effects [16] (see Section 2.1.2.1) as well as to tunable waveguiding structures and functional elements in photonic crystals [17][18][19][20][21] (see Section 2.1.3). In addition, liquidcrystal infiltrated photonic crystals may provide a novel form of (tunable) disorder [14] which-besides studying fundamental aspects of wave propagation such as Anderson localization-may find applications in the testing of random numbers [22,23].…”
Section: H N K ( R) → Exp(i N K ) H N K ( R) (216)mentioning
confidence: 99%
“…In particular, photonic band structure computations have shown that controlling optical anisotropies allows for the opening and closing of complete threedimensional photonic band gaps in liquid crystal infiltrated PBG materials [14]. Later, the concept of tunable photonic band structures has been extended to tunable superrefractive effects [16] (see Section 2.1.2.1) as well as to tunable waveguiding structures and functional elements in photonic crystals [17][18][19][20][21] (see Section 2.1.3). In addition, liquidcrystal infiltrated photonic crystals may provide a novel form of (tunable) disorder [14] which-besides studying fundamental aspects of wave propagation such as Anderson localization-may find applications in the testing of random numbers [22,23].…”
Section: H N K ( R) → Exp(i N K ) H N K ( R) (216)mentioning
confidence: 99%
“…This is an alternative to the known concept of tunable lasers where the resonator itself is modified, e.g. by thermal, electrooptical (using liquid crystals) or micromechanical means [16][17][18][19] to tune a given mode to have the desired frequency. One of the advantages may be that modes selected by injection seeding can be better pre-engineered to meet the desired fundamental (e.g., cavity QED) or application purposes [10].…”
Section: Introductionmentioning
confidence: 99%
“…Tunability has been explored through electrical [24][25][26][27][28][29], magnetic [8,29,[30][31][32], thermal [30,33], and mechanical control [34]; through immersion in coherent atomic gases [35], and through variations in the angle of incidence of the optical beam [36]. Magnetic tunability studies have consisted of theoretical band gap analysis focusing on dielectric permittivity or magnetic permeability control and their effect on gap width, band gap center wavelength [8,29,31,32], and the effect of magnetic fields on the superconducting state in photonic crystals composed of copper oxide high-temperature superconductors [30].…”
Section: Introductionmentioning
confidence: 99%